1997
DOI: 10.1074/jbc.272.17.11021
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Biochemical Characterization of a Protein-palmitoyl Acyltransferase from Human Erythrocytes

Abstract: Protein palmitoylation involves the post-translational attachment of palmitate in thioester linkage to cysteine residues of proteins. The labile nature of the thioester linkage makes possible the palmitoylation-depalmitoylation cycles that have emerged in recent times as additions to the repertoire of cellular control mechanisms. However, detailed understanding of these cycles has been limited by the lack of knowledge of the transferases and thioesterases likely to be involved. Here, we describe the purificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…It has been shown that myristoyl peptides bind membranes with a Gibbs free binding energy of around 8 kcal/mol [73], whereas the more hydrophobic palmitoylCoA binds more strongly, resulting in around 15-fold greater partitioning of palmitoylated substrates to the membrane [72]. Palmitoyl acyltransferases have only recently been characterised, but in most cases studied they also localise to membranes [74,75]. This could be one mechanism by which certain fatty acyl-CoA substrates are made unavailable to NMT in the cell.…”
Section: Nmt Regulationmentioning
confidence: 99%
“…It has been shown that myristoyl peptides bind membranes with a Gibbs free binding energy of around 8 kcal/mol [73], whereas the more hydrophobic palmitoylCoA binds more strongly, resulting in around 15-fold greater partitioning of palmitoylated substrates to the membrane [72]. Palmitoyl acyltransferases have only recently been characterised, but in most cases studied they also localise to membranes [74,75]. This could be one mechanism by which certain fatty acyl-CoA substrates are made unavailable to NMT in the cell.…”
Section: Nmt Regulationmentioning
confidence: 99%
“…Despite the accumulation of evidence showing that the palmitoylation of various proteins, including RAS, is critical for their biologic functions, the enzymes involved in this process are still poorly understood. Several groups have sought to purify PAT enzymes (Gutierrez and Magee, 1991;Liu et al, 1996;Das et al, 1997;Ueno and Suzuki, 1997;Hiol et al, 2003), unfortunately none have provided any examples of bona fide human Pat enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The reversibility of protein-palmitate bonds has been demonstrated by the rapid turnover of the palmitoyl group and may be caused by the relative lability of the thioester linkage (8 -10). Protein palmitoylation and depalmitoylation reactions are considered to be primarily enzymatic and catalyzed by unidentified membrane-bound palmitoyl acyltransferases (11,12) and by cytoplasmic and lysosomal forms of palmitoyl thioesterases (13)(14)(15), respectively. Regulation of the protein palmitoylation and depalmitoylation cycle is thought to be important in regulating protein localization, conformation, protein-protein interaction, and activity (16 -18).…”
mentioning
confidence: 99%